NIST CSF 2.0: Your essential introduction to managing cybersecurity risks - Pattison, Andrew (IT Governance Publishing, 2025)
A concise introduction to the NIST CSF 2.0 The NIST CSF (Cybersecurity Framework) 2.0 is designed to protect organizations from cyber attacks. Although the CSF was developed to help US organizations involved in infrastructure to systematically organize their critical activities and ensure they remain up to date, Version 2.0 states that “ The CSF is designed to be used by organizations of all sizes and sectors, including industry, government, academia, and nonprofit organizations, regardless of the maturity level of their cybersecurity programs.” NIST 2.0 is an effective and flexible framework that is well-known across the US, and increasingly across the rest of the world. It also aligns closely with ISO 27001 and ISO 22301, and all three standards can operate concurrently. This book will help you understand how to: Begin implementing the NIST CSF 2.0 in your organization Build a cybersecurity program, adapt an existing one, or review existing security practices Integrate the NIST CSF 2.0 with other frameworks such as ISO 27001 and ISO 22301 Organizations that comply with the NIST CSF 2.0, ISO 27001, and ISO 22301 demonstrate their commitment to cybersecurity to current and prospective stakeholders.